A Textbook Analysis of “My Next Words” for the Fifth Grade Elementary School - Pipit Novianti; Evi Karlina Ambarwati (Universitas Pendidikan Mandalika, 2023)
Textbooks are one of the materials used in the teaching and learning process. Textbooks have many benefits and important components in achieving the goals of the needs of learners (Cunningsworth, 1995). A qualitative method was conducted in this study. In brief, a descriptive qualitative research design was used to analyze and investigated an English textbook entitled Student’s Book “My Next Words” for Elementary School published by the Ministry of Education and Culture. The research data were collected from the content of the English textbook. To reveal the English textbook's content and appropriateness, this present study explored and researched an English textbook entitled Student’s Book